What’s trending? #sexual assault: an exploratory study of social media coverage of teen sexual assaults - Wellman, Ashley (Criminology, criminal justice, law & society, 2017)
Social media play a significant role in the lives of many, particularly teenagers. For heavy users of social media, great significance is attributed to the messages posted in the virtual world. In the aftermath of sexual assault, victims, offenders, friends, family, the community, and virtual strangers have the ability to weigh in on the assault. Little research has explored these societal reactions on social media. The current exploratory, qualitative study examines social media responses to four highly publicized cases ofteenage sexual assault: Daisy Coleman, Jane Doe, Audrie Pott, and Jada. Five major themes were identified via thematic analysis, including victimblaming/shaming, offender support, family/survivor utilization, victim support, and offender blaming. A thematic map, definitions, and examples of these themes are provided within. Consistent with commonly held rape myth beliefs, victim blaming/shaming appeared as the most common reaction on social media, witha large parallel response of offender support. Victim support emerged as a popular theme only after family members and the survivor spoke out, facts of the rape emerged, and media attention grew. The theme of offender blame was the most difficult to find amid the messages targeting the victim. The discussion highlights the significance of major trends, relationships among themes, and the potential repercussions of such social media presentations. Additional recommendations for education on the reality of sexual assault and awareness of healthy and responsible social media usage are disclosed.